If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(-4) = 2x Multiply -1 * -4 6 + 4 = 2x Combine like terms: 6 + 4 = 10 10 = 2x Solving 10 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 10 + -2x = 0 Add '-10' to each side of the equation. 10 + -10 + -2x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = 0 + -10 -2x = 0 + -10 Combine like terms: 0 + -10 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| 1+3x=-15+5x | | 3(3x-2)+15= | | 3/2(3)+2= | | 6r^3+2r^3-r^2= | | -4=-8-m | | (4x-22)+(7x+4)=180 | | 20x+34+5x+21=12x-14+5x+21 | | f(x)=47x-41 | | -3=-4+4-4 | | 8+5(3c-1)=39c-13 | | 5x+21+20x+34=12x-14+5x+21 | | 14=6+zover-2 | | 6x^5-48x^2+96x=0 | | 2x+11=x+22 | | .16+21=c | | -10-39= | | 20x+34=12x-14+5x+21 | | 5(y-2)-4(y+1)=3 | | 2x+11=x+11 | | 9x+3+13x+1=180 | | 3-3n=42 | | 9x+3+12x+1=180 | | 0=-12n+12n | | -2z^2+4z+2z^2= | | 10-4x+6-2x=2x | | g(3y)=x-2x^2 | | 3x-17=9x-20 | | 0.15m=0.5m+40 | | 4x^2+12x+17=0 | | 7-x^2=19 | | g+18=16g+3 | | (1+2)2x(3-1)2= |